Synthesis and characterization of visible light-driven W-doped Bi2MoO6 photocatalyst and its photocatalytic activities - Phuruangrat A. (2017)
© 2017 Elsevier B.V. W-doped Bi 2 MoO 6 photocatalyst has been synthesized by hydrothermal method. It exhibits an orthorhombic Bi 2 MoO 6 nanoplates with the increase of the W doping amount from 0 to 3%. Among these W-doped samples, 3% W-doped Bi 2 MoO 6 sample shows the degradation efficiency of 100% for Rhodamine B under visible light irradiation within 140 min which is higher than pure Bi 2 MoO 6 nanoplates. The calculated apparent reaction rate constant for the 3% W-doped Bi 2 MoO 6 of 0.027 min −1 is 1.69 times of pure Bi 2 MoO 6 photocatalyst (0.016 min −1 ).